Adaptation of candidate vaccine strains of South African Territories (SAT) type foot-and-mouth disease virus to suspension cell culture - Bastos, Armanda D.S. (University of Pretoria, 2024)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2023.